Screening and Isolation of Cellulolytic Bacteria from Gut of Black Soldier Flays Larvae (Hermetia illucens) Feeding with Rice Straw - Ateng Supriyatna; Ukit Ukit (Biosaintifika: Journal of Biology & Biology Education, 2016)
A research on screening and isolation of cellulolytic bacteria from the gut of larvae Black Soldier treated rice straw feed has been conducted. The purpose of this study is to get the type of cellulolytic bacteria from the gut of larvae and bacteria that have the highest potential to degrade cellulose. Screening and isolation method applied by using intestinal larvae obtained from larval gut vortex at a speed of 1500 rpm. Furthermore, dilution graded from 1 to 10 and grown in media CMC (carboxyl methyl cellulose) at 37 0C and incubated for 48 hours. Observations were made based on the characteristics of the microscopic, macroscopic, biochemical test, cellulolytic activity and the activity of cellulase enzymes selected bacteria. The results showed a 9 cellulolytic bacteria from the gut of the larvae. Bacillus sp. is a bacteria that have the highest potential with cellulolitic activity 2.1 mm (dz/dk), the exponential phase of hour at the 24th, and cellulase enzyme activity of 0.4 U/mL at pH 7 and 0.41 U/mL at pH 8.This research showed that the Black Soldier Flays Larvae (Hermetia illucens) have competencein organic waste degradation, because in Black Soldier Flays Larvae’s gut, cellulolitic enzyme is produced by cellulolitic bacteria, specially Bacillus sp,How to CiteSupriyatna, A., Ukit, U. (2016). Screening and Isolation of Cellulolytic Bacteria from Gut of Black Soldier Flays Larvae (Hermetia illucens) Feeding with Rice Straw. Biosaintifika: Journal of Biology Biology Education, 8(3), 314-320.